On representation of integer-valued random measures by means of stochastic integrals with respect to the Poisson measure - Grigelionis, B. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. Григелионис. О представлении целочисленных случайных мер как стохастических интегралов по пуассоновской мереB. Grigelionis. Apie atsitiktinių matų su sveikomis reikšmėmis išreiškimų stochastiniais integralais Puasono mato atžvilgiu